(untitled) (Asian Journal of Agriculture, 2020)
Abstract. Alane F, Rahale-Bouziane H, Fadjer Z. 2020. Feed quality of some populations and varieties of sorghum. Asian J Agric 4: 5-13. This research aimed to characterize some local populations and those from ACSAD through two trials. The Sudan population is believed to be better than the other two local populations. There is one with an average height of 55.07 cm and an average number of tillers per square meter 128/m², that offers a green and dry yield of 5311.47 g/m² and 497.2 g/m² respectively. In the second test, the comparison of the chemical composition of the pasty milky and hard grain stages did not register a big difference. CP was almost the same (6.66% and 6.1%). The varieties Masser 17, Ezzera, and Biofuel from milky-pasty stage to hard grain stage has their cellulose rate decrease. The maturity of the seed is reached between 82 and 92 days after sowing and their sizes vary between 71 cm and 1.26 m. The average cellulose level of milky-pasty populations is 26.08% and the hard-grain stage is 28.44%. The analysis of the principal components at the hard grain stage has constituted two groups: Kherssi, Beida Adrar, Tougourte, Ain Sallah. Ezzera, Biofuel, Masser17, El Menea. Greater diversity in the chemical composition of the stems, than in those of the leaves more digested was observed.